Are graduate social work students mindful?. Issue 1 (2nd January 2016) - Kessen, Christine; Turner, Kielty
ABSTRACT: Does the current common practice of traditional teaching of social work coupled with experiential learning in field placements foster mindfulness in graduate students? Using the Mindful Attention Awareness Scale (Brown & Ryan, 2003) a cohort of 100 MSW (Master of Social Work) students were surveyed on their development of mindfulness during their first and last semesters. Instead of an increase in mindfulness, a significant decrease was found. During qualitative interviews, students reported multiple opportunities within their MSW experience to learn and practice mindfulness. Yet, these opportunities were not sufficient to raise the mindfulness level of the MSW cohort. Future studies which identify effective means to increase student mindfulness are recommended.